(q, p)-Mixing Bloch maps - Jiménez-Vargas Antonio; Ruiz-Casternado David (Demonstratio Mathematica, 2025)
As a Bloch variant of (q,p)\left(q,p)-mixing linear operators, we introduce the notion of (q,p)\left(q,p)-mixing Bloch maps. We prove Pietsch’s domination theorem and Maurey’s splitting theorem in this Bloch context, following the corresponding results from the linear case.